1995
DOI: 10.1007/bf01565470
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of meniscal tears in acute anterior cruciate ligament (ACL) ruptures and in chronic ACL-deficient knees

Abstract: Through the retrospective study of 1103 reconstructions of the anterior cruciate ligament (ACL) performed between 1984 and 1993, we try to outline the natural history of meniscal tears in acute lesions and in chronic insufficiency of the ACL. According to a more accurate evaluation of the clinical evolution, ACL-deficient knees can be classified into four different stages: acute, subacute, subchronic and properly chronic laxities. While acute injuries show a higher rate of lateral meniscus tears, chronic laxit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 12 publications
8
120
2
2
Order By: Relevance
“…First, surgical timing must be discussed. Most surgeons would agree that ACL reconstruction should only be performed once full motion has been regained, unless in the setting of a tibial eminence fracture or a bucket-handle meniscus tear [46,47] (Cipolla M KSSTA 1995, Shelbourne KD AJSM 1991). Recently a report of increased risk of meniscal damage with delay in treatment of greater than 12 weeks may indicate that these injuries ought to be treated more urgently, however [48••].…”
Section: Operativementioning
confidence: 99%
“…First, surgical timing must be discussed. Most surgeons would agree that ACL reconstruction should only be performed once full motion has been regained, unless in the setting of a tibial eminence fracture or a bucket-handle meniscus tear [46,47] (Cipolla M KSSTA 1995, Shelbourne KD AJSM 1991). Recently a report of increased risk of meniscal damage with delay in treatment of greater than 12 weeks may indicate that these injuries ought to be treated more urgently, however [48••].…”
Section: Operativementioning
confidence: 99%
“…D. Guenther, V. Swami, S. S. Dhillon, J. L. Jaremko (&) Department of Radiology and Diagnostic Imaging, University of Alberta, 2A2.42 Walter Mackenzie Health Sciences Centre, Edmonton, AB T6G 2B7, Canada e-mail: jjaremko@ualberta.ca are associated with increased risk of injury to menisci, which normally transmit load and absorb shocks between the femur and tibia [37]. With each episode of giving way, meniscal tears can become more complex and less amenable to repair [8]. Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…With each episode of giving way, meniscal tears can become more complex and less amenable to repair [8]. Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction. Although the treatment of ACL tears in skeletally immature patients remains controversial [33], the risk of physeal injury and resulting growth disturbance from ACL repair to a patient with open physes is now thought to be small [15,22], and many centers (including our institution) opt for prompt reconstruction before skeletal maturity [9,16,20,25,31,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…However, several reports have found similar patterns of meniscal injury in the anterior cruciate deficient knee. 2,3 In those reports, in acute cases of ACL injury the rates of meniscal injury were 28.5 to 44% for the medial meniscus and 56 to 61% for the lateral meniscus. In chronic cases the rate of the medial meniscal injury was 70% to 74.5% and that of the lateral meniscus was 30% to 41.6%.…”
Section: Discussionmentioning
confidence: 95%